Cytotoxic effect of Hemigraphis alternata (Burm. F.) T. Anderson leaf extract on Allium cepa root tip. - Hilal, Fouzia (Journal of Drug Delivery and Therapeutics, 2019)
Cytotoxicity is a major subject in pharmaceutical studies relevant to the area of cancer research. Low cytotoxicity to healthy cells and high cytotoxicity to cancerous cells is the ultimate goal of many chemotherapy drugs. Hemigraphis alternata (Burm. F.) T. Anderson of Acanthaceae family is an exotic plant adapted to India, a versatile tropical low-creeping perennial herb .The leaves of Hemigraphis alternata were collected .50% and 25% aqueous extracts of the plants were prepared from fresh leaves. Onion root tips treated with each concentration were used for cytology study. Mitotic index (M.I.) and various chromosomal abnormalities were studied. Present study showed lower Mitotic index frequency in roots treated with extract as compared to control. Chromosome aberrations were observed in all stages of mitosis. The most frequently observed abnormalities were nuclear lesions, chromosome stickiness, multipolar anaphase, chromosome laggards, stellate chromosome etc..Keywords: Cytotoxicity, Mitotic index, Chromosomal aberrations, Hemigraphis alternata.